Optimalisasi Desa Lawan Covid-19 melalui Kegiatan Promotif dan Preventif Kepada Masyarakat di Perumahan Taman Lestari, Kota Batam, Kepulauan Riau - Emi Antika Sari; Frita Handayani Habeahan; Nanik Saryati Hutabarat (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2021)
Promotional and preventive activities for the community at Perumahan Taman Lestari, Kibing Village, Batam City, Riau Islands are expected to provide scientific, accurate, and reliable knowledge and understanding that will help the community to quickly implement government appeals and directives to reduce the spread of Covid-19. Methods of activity are (a) site survey; (b) coordination with local government; (c) preparation of activity programs; (d) implementation of program activities; and (e) evaluation of program activities. The results of activities carried out by a team of village volunteers against Covid-19, Riau University at Perumahan Taman Lestari RW 13, Kibing Village, Batam City, Riau Islands are guarding village entrance posts, building handwashing stations, spraying disinfectants in community residences and places. Public places, making cloth masks, distributing hand sanitizers and cloth masks, distributing cash social assistance stages I, II, and III of making banners for mandatory masks appeals to people to always carry out Covid-19 health protocols such as staying at home, always wearing masks, keeping their distance safe, and wash your hands with soap. Thus, it can be concluded that promotive and preventive activities can provide knowledge and understanding of the community to carry out government appeals and directives to reduce the spread of Covid-19.